"Bring Your Own Device" (BYOD): The Future of Field-Based Patient-Reported Outcome Data Collection in Clinical Trials?. (November 2015) - Gwaltney, Chad; Coons, Stephen Joel; O'Donohoe, Paul; O'Gorman, Hannah; Denomey, Matthew; Howry, Cindy; Ross, Jennifer
Field-based patient-reported outcome (PRO) assessments, including measures of signs, symptoms, and events that are administered outside of the research clinic, can be critical in evaluating the efficacy and safety of new medical treatments. Collection of this type of data commonly involves providing subjects with stand-alone electronic devices, such as smartphones, that they can use to respond to assessments in their home or work environment. Although this approach has proven useful, it is also limited in several ways: For example, provisioning stand-alone devices can be costly for sponsors, and requiring subjects to carry a device that is exclusively dedicated to the study can be burdensome. The "Bring Your Own Device" (BYOD) approach, in which subjects use their own smartphone or Internet-enabled device to complete field-based PRO assessments, addresses many of these concerns. However, the BYOD model has its own limitations that should be considered. In this article, representatives of the ePRO Consortium review operational, privacy/security, and scientific/regulatory considerations regarding BYOD. We hope that this review will allow researchers to make informed decisions when choosing methods to collect field-based PRO data in future clinical trials. Additionally, we hope that the discussion in this article will establish a research agenda for further examination of BYOD approaches.